Verificação de altas capacidades em crianças e adolescentes em situação de acolhimento no Brasil e na Espanha - Colozio, Amanda Rodrigues de Souza (Universidade Federal de São Carlos, 2021)
Getting to know the places where people in poverty live, under risks, disadvantages and dangers, trying to find some talent for a promising reality is auspicious. To stand out positively in contexts of risk, proves that the person has a potential to be developed, despite the unfavourable environmental factors. The present research is divided into two studies. Study 1 had the objective of identifying indicators of high abilities in children and adolescents in Residential Care Institutions in a Canary Island, Tenerife, in Spain; to characterise the participants; and to know how the assistance is organised in the residential care institutes. Study 2 aimed to identify indicators of high abilities in children and adolescents in residential institutions in the interior of the State of São Paulo; to present the profile of the teachers of these students; and finally, to attend as enrichment the students indicated as having high abilities. The methodological design of the research was exploratory and descriptive. For the study 1- Indication of high abilities in Spain, 26 children and/or adolescents from 15 residential care institutions throughout the island of Tenerife and 22 educators from these institutions participated. The data collected were analysed in two stages, namely: Stage 1. Indication of high abilities and characterisation, MATRICES-TAI, SENA and attendance; and Stage 2. Structure and Functioning of the residential care institutions. The instruments used were: Escala de apreciación para educadores/as; Instrumento Sistema de Evaluación de Niños y Adolescentes (SENA); MATRICES - Test Adaptativo Informatizado (TAI), and Questionnaire sobre la Unidad Orgánica de Infancia y Familia del IASS. As results, it was obtained in Study 1, 6 (six) fostered with indications of high abilities, being 4 (four) boys and 2 (two) girls in the areas of general intelligence, creativity, socio-affective and verbal. These 6 students, together with 4 previously identified with intelligence tests, were referred to two programmes: the Comprehensive Programme for High Abilities (PIPAC) and Tagoror, carried out at the University of La Laguna, Tenerife. In Study 2 - Indication of high abilities in Brazil, participated 14 schools, 94 teachers, 5 institutions of Reception, 12 professionals of the institutions and 30 receivers of two cities (A and S) in the interior of the state of São Paulo. The instruments used were: Guide for Observation of Students in the Classroom (Guide); Questionnaire on the profile of the teacher, and the Enrichment, based on the interests and the formation of positive self-concept. The data collected was in three stages: Stage 1. Indication of high abilities in students in county A and S; Stage 2. Teacher profile questionnaire; Stage 3. Enrichment offered to the student. As for the results, the Guide applied with the teachers returned with 1 (one) fostered (A) indicated with high abilities in three domains: High Ability in General, Verbal and Socio-affective Intelligence. The other respondents were not indicated as outstanding in any domain. As for the response of the professionals, 4 (four) were indicated as gifted in General Intelligence, Creativity and Socio-affective. Respondent A was indicated and referred to care in the form of enrichment aimed at developing his interests and contributing to the formation of his positive self-concept.

Conocer los lugares donde viven las personas en situación de pobreza, bajo riesgos, desventajas y peligros, tratando de encontrar algún talento para una realidad prometedora es auspicioso. Destacar positivamente en contextos de riesgo, demuestra que la persona tiene un potencial de desarrollo, a pesar de los factores ambientales desfavorables. La presente investigación se divide en dos estudios. El estudio 1 tenía como objetivo identificar indicadores de altas capacidades en niños y adolescentes en instituciones de atención residencial en una isla canaria, Tenerife, España; caracterizar a los participantes; y conocer cómo se organiza la atención en los institutos de atención residencial. El estudio 2 tuvo como objetivo identificar indicadores de altas capacidades en niños y adolescentes de Instituciones de Acogida Residencial del interior del Estado de São Paulo; presentar el perfil de los profesores de estos alumnos; y, finalmente, atender en forma de enriquecimiento al o los alumnos señalados como de altas capacidades. El diseño metodológico de la investigación fue exploratorio y descriptivo. Para el estudio 1- Indicación de altas capacidades en España, participaron 26 niños y/o adolescentes de 15 instituciones de atención residencial de toda la isla de Tenerife y 22 educadores de estas instituciones. Los datos recogidos se analizaron en dos etapas, a saber: Etapa 1. Indicación de altas capacidades y caracterización, MATRICES-TAI, SENA y asistencia; y Etapa 2. Estructura y funcionamiento de las instituciones de atención residencial. Los instrumentos utilizados fueron: Escala de apreciación para educadores; instrumento Sistema de Evaluación de Niños y Adolescentes (SENA); MATRICES - Test Adaptativo Informatizado (TAI), y Cuestionario sobre la Unidad Orgánica de Infancia y Familia del IASS. Como resultados, se obtuvo en el Estudio 1, 6 (seis) fomentados con indicios de altas capacidades, siendo 4 (cuatro) niños y 2 (dos) niñas en las áreas de inteligencia general, creatividad, socio-afectiva y verbal. Estos 6 alumnos, junto con 4 identificados previamente con pruebas de inteligencia, fueron indicados a dos programas: Programa Integral para Altas Capacidades (PIPAC) y Tagoror, llevados a cabo en la Universidad de La Laguna, Tenerife. En el Estudio 2 - Indicación de altas capacidades en Brasil, participaron 14 escuelas, 94 profesores, 5 (cinco) instituciones de Acogida, 12 profesionales de las instituciones y 30 receptores de dos ciudades (A y S) del interior del estado de São Paulo. Los instrumentos empleados fueron: Guía de observación de los alumnos en el aula (Guía); Cuestionario sobre el perfil del profesor, y el Enriquecimiento, basado en los intereses y la formación del autoconcepto positivo. Los datos recogidos se dividieron en tres etapas: Etapa 1. Indicación de altas capacidades en los alumnos del condado A y S; Etapa 2. Cuestionario del perfil del profesor; Fase 3. Enriquecimiento ofrecido al estudiante. En cuanto a los resultados, la Guía aplicada con los profesores volvió con 1 (uno) fomentado (A) indicado con altas habilidades en tres dominios: Alta capacidad en inteligencia general, verbal y socio-afectiva. Los demás encuestados no fueron señalados como sobresalientes en ningún ámbito. En cuanto a la respuesta de los profesionales, 4 (cuatro) fueron indicados como superdotados en Inteligencia General, Creatividad y Socioafectiva. Se indicó y derivó al demandado A a una atención en forma de enriquecimiento destinada a desarrollar sus intereses y contribuir a la formación de su autoconcepto positivo.
Verificación de altas capacidades en niños y adolescentes en situaciones de acogida en Brasil y España
Verification of high capacities in children and adolescents in foster home situations in Brazil and Spain
Keywords: Educação Especial; Altas capacidades; Vulnerabilidade social; Instituição de acolhimento; Identificação; Atendimento; Special Education; High abilities; Vulnerability; Foster Home; Identification; Special Service; Educación Especial; Vulnerabilidad; Institución de acogimiento; Identificación; Atendimiento; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO